The Role of Brand Image in Mediating the Influence of Country of Origin Image and Price on Purchasing Decisions (Study Case on Car Credit Products PT. Maybank Indonesia Finance) - Melitina Tecoalu; Saparso; Fernandes (Budapest International Research and Critics University, 2021)
The development of transportation, especially four-wheeled vehicles, is very fast, which can cause finance companies to move dynamically. The development of finance companies today leads to intense competition. The increasing need for cars and other necessities of life drives people to buy cars in cash or credit financing (Leasing). One of the car loan financing companies in Indonesia is PT. Maybank Indonesia Finance. Before purchasing the product they want, some consumers will assess and see where this product company comes from. In addition to COO, price is also one of the determining elements for consumers to purchase a product or service they want. When the image of the country of origin is good, and the price set is cheap, it will make consumers perceive the idea of the product and will later influence purchasing decisions. Therefore, this study wanted to examine the role of brand image in the mediating country of origin image and price on purchasing decisions. This research was conducted by non-probability sampling method with purposive sampling type. Researchers distributed questionnaires to 100 Maybank Finance consumer respondents in Indonesia who had purchased Maybank Finance car loans in 2018-2020. The analysis results conclude that the image of the country of origin has no positive and significant effect on buying decisions. Price has a positive and significant effect on purchasing decisions. The idea of the country of origin has a positive and significant effect on brand image. Price has a positive and significant effect on brand image. Brand image has a positive and significant effect on purchasing decisions. Brand image mediates the idea of the country of origin on purchasing decisions. Brand image negotiates price on buying decisions.